Trauma Responses in Social Choreography: Accessing Agency and Opportunities for Healing through Mindful Embodiment - Catherine Cabeen (Arts, 2023)
This article responds to the questions: how does trauma that is long-held in the body affect social choreography? And how can awareness of this intersection guide us towards individual and collective healing practices? Embodied trauma responses, commonly referred to as fight, flight, freeze, and dissociation, initially function as potentially lifesaving responses to external threats but all too often become engrained in how people move through the world and relate to one another. When these patterns of engagement become habituated, they affect the improvisational scores inherent to social choreography. Exploring trauma responses through the lens of social choreography invites increased awareness of how these patterns of behavior affect our relationships and communities. Through this awareness, the possibility of agency is increased. This essay continues the work of somatic and cultural scholars Resmaa Menakem, Staci K. Haines, and Zhiwa Woodbury, among others, whose research points to multiple continuums between how trauma is individually embodied and cultural dynamics we are experiencing globally. Drawing on the somatic work of Peter Levine and Bessel Van der Kolk, whose theories have revolutionized trauma healing, this essay offers accessible pathways to trauma sensitivity that readers can experiment with to consciously refine their own roles in social choreographies ranging from interpersonal to cultural interactions.